Geschichtsbilder in der deutsch-polnischen Grenzregion [Historical images in the German-Polish border region] - Schultz, Helga (Studia Historiae Oeconomicae, 2009)
Beyond political rhetoric, the relationship between Germans and Poles is never easy, and its fragility should not surprise anyone with deeper knowledge. In the following, we will look at the development of historical images of German-Polish relations in the border region, i.e. historical images that were largely determined by the special relationship between Poland and the GDR, which is often disqualified today as a "prescribed friendship". Taboos played a major role in this. It is a bold thesis that these taboos were ultimately beneficial, and that breaking down the taboos in the fight against the "blank spots" opened the floodgates for ideas that harbor conflicts. The unconditional truth is not always the best. And above all: what is the truth? The historian knows that it is not unambiguous and that there can be several of them.